PENGARUH SENAM KAKI TERHADAP INTENSITAS NYERI PADA PENDERITA DIABETES MELLITUS TIPE 2 DI POSYANDU LANCAR BAHAGIA DESA GLEMPANG KECAMATAN MAOS KABUPATEN CILACAP - Ade Suryana; Adiratna Sekar Siwi; Danang Tri Yudono (Yakpermas Press, 2023)
Diabetes Mellitus (DM) type 2 is never separated from pain in the feet caused by peripheral neuropathy. An alternative to reduce pain in type 2 DM sufferers is diabetic foot exercise. Diabetic foot exercise is a simple physical exercise that can be applied at any time. Diabetic kako exercise if done regularly can reduce pain intensity to the maximum and can also reduce the risk of osteoporosis. This study aims to determine the effect of foot exercise on pain intensity in patients with type 2 DM. This study used a pre-experimental method with a one group pretest-posttest design approach. Samples were taken with a total sampling of 27 respondents. Respondents came from the experimental group of 27 respondents. The research instruments used were videos, SOPs, Numerical Rating Score (NRS) sheets and observation sheets. The data analysis used in this research is the Wilcoxon test. Data collection was carried out after passing the ethical test. The results showed that there was an effect of diabetic foot exercise on pain intensity in the experimental group with a p-value of 0.000. The conclusion of this study is that diabetic foot exercises are effective in reducing pain intensity in type 2 DM patients.